2020
DOI: 10.9734/ijbcrr/2020/v29i530191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antiplasmodial and Antioxidant Activities, Total Phenolics and Flavonoids Content, and Toxicological Profile of Cola millenii K. shum (Malvaceae)

Abstract: Aims: This study was designed to assess antiplasmodial and antioxidant activities in relation to phytochemical contents and toxicological profile of crude extracts of Cola millenii leaves. Place and Duration of Study: The study was carried out from April 2015 to November 2018 at University of Abomey-Calavi, Laboratory of Biochemistry and Bioactives Natural Products and Laboratory of Infectious Vector-borne Diseases. Methodology: Phytochemical screening of aqueous and ethanolic crude extracts was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…For example, a study conducted in southern Benin has reported that medicinal plant species such as Dissotis rotundifolia, Ehretia cymosa Thonn, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl are commonly used by populations for malaria treatment [10]. Furthermore, the use of these medicinal plants as malaria remedies has been validated by in vitro evaluation of their antiplasmodial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study conducted in southern Benin has reported that medicinal plant species such as Dissotis rotundifolia, Ehretia cymosa Thonn, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl are commonly used by populations for malaria treatment [10]. Furthermore, the use of these medicinal plants as malaria remedies has been validated by in vitro evaluation of their antiplasmodial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the drug-exposed and unexposed parasites were genotyped using Msp1 and Msp2 markers. 4) Beninese medicinal plants including Dissotis rotundifolia, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl, which have been previously found to be active against asexual P. falciparum [11][12][13][14], were used. Furthermore, the crude extract of the antimalarial plant species Ehretia cymosa Thonn and a compound encoded CpE2, previously extracted from this plant (unpublished data), was screened.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation